Identifying Strategies to Advance Health Equity through Action on Social Determinants of Health and Human Rights for Street-Connected Children and Youth in Kenya - Lonnie Embleton; Pooja Shah; Allison Amin Gayapersad; Reuben Kiptui; David Ayuku; Paula Braitstein (Harvard FXB Center for Health and Human Rights, 2020)
Despite the fact that street-connected children and youth (SCY) in low- and middle-income countries experience numerous social and health inequities, few evidence-based policies and interventions have been implemented to improve their circumstances. Our study analyzed strategies to advance health equity through action on the social determinants of health (SDH) for SCY in Kenya based on General Comment 21 of the United Nations Committee on the Rights of the Child. To identify policies and interventions, we analyzed archival newspaper articles and policy documents and elicited ideas from a diversity of social actors across Kenya. Our results identified three types of policies and interventions: repressive, welfare oriented, and child rights based. We then situated these strategies within the World Health Organization's conceptual framework on SDH inequities to understand their mechanism of impact on health equity. Our results demonstrate that a child rights approach provides a strong avenue for advancing health equity through action on the SDH for SCY in Kenya. As a result of these findings, we developed a checklist for policy makers and other stakeholders to assess how their policies and interventions are upholding human rights, addressing needs, and working to advance health equity for SCY.